Bоспи- тание в социуме толерантности к детям-инвалидам с психофизическими наруше- ниями - Muller Ruvimovich, Alexander; Viktorovna, Lisovskaya Tatiana (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
The article considers issues of handicapped children socialization. It shows the leading role of training children with the apparent disturbance of development in social and living and communicative skills. Big problem is the organization of employment for this category of disabled people and questions of society tolerance in connection with this problem. The article presents the Interregional Project on training society for tolerance to persons with disturbance of development. The aim of the present Project is, on the one hand, to teach the society to tolerant attitude towards people with development problems and, on the other hand, to improve the handicapped children’s skills of social behavior and to organize support of families with children with disturbance of development.